A Review Paper on Application of PCR-ELISA in the Molecular Diagnosis (International Journal of Innovative Research in Engineering & Management, 2023)
PCR-ELISA (Enzyme-linkedlinked  immunosorbent assay - polymerase chain reaction),  immunodetection method used to count the PCR amplified  creation just after the halt of biotinylated DNA on the  microtiter bowl. Amplification, immobilization, and  detection are the three phases of the synthesis chained  response - enzymes coupled immunoassay assay  procedure. PCR-ELISA is more sensitive than the  conventional PCR method, it detects nucleic acids rather  than protein with the lesser detection time and tinier  analytical time. Due to its high sensitivity and specificity,  it has potential application as a detection tool in the  numerous industries like; agricultural, food industry,  veterinary and medical. PCR-ELISA in industries used for  the detection, diagnosis and quantitative monitoring.
Keywords: Applications; Diagnosis; Molecular